2018
DOI: 10.1111/gcb.14470
|View full text |Cite
|
Sign up to set email alerts
|

Tree resilience to drought increases in the Tibetan Plateau

Abstract: Forests in the Tibetan Plateau are thought to be vulnerable to climate extremes, yet they also tend to exhibit resilience contributing to the maintenance of ecosystem services in and beyond the plateau. So far the spatiotemporal pattern in tree resilience in the Tibetan Plateau remains largely unquantified and the influence of specific factors on the resilience is poorly understood. Here, we study ring‐width data from 849 trees at 28 sites in the Tibetan Plateau with the aim to quantify tree resilience and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…DNA repair and disease-resistance pathways have been found to play a crucial role in the highland adaptation of Tibetan highland plants [46,54]. In the present study, we detected significant expressions of many unigenes related to pathogen response that contained either a nucleotide binding (NB)-ARC domain or a leucine-rich repeat (LRR) domain, which were present in most resistance (R) proteins [55][56][57].…”
Section: F Macclureana Has Presumably Evolved An Integrated Mechanismentioning
confidence: 53%
“…DNA repair and disease-resistance pathways have been found to play a crucial role in the highland adaptation of Tibetan highland plants [46,54]. In the present study, we detected significant expressions of many unigenes related to pathogen response that contained either a nucleotide binding (NB)-ARC domain or a leucine-rich repeat (LRR) domain, which were present in most resistance (R) proteins [55][56][57].…”
Section: F Macclureana Has Presumably Evolved An Integrated Mechanismentioning
confidence: 53%
“…outside the QTP) triggered the expressions of these unigenes. Warmer temperatures can greatly reduce flowering synchrony among individuals from 72 woody and herbaceous species [53]. It was also reported that P. oceanica, a highly clonal and long-lived species, massively bloomed after a simulated heatwave [45].…”
Section: Discussion Activated Hd3a Expression Probably Accelerates Flmentioning
confidence: 99%
“…Robust quantification of the vulnerability and resilience of forested ecosystems to environmental changes is essential for better understanding how climate change affects tree performance and mortality (Allen et al , Hartmann et al ) as well as for assessing climate change impacts on forest health (Trumbore et al ) and ecosystem services (Theurillat and Guisan , Elkin et al ). Traditionally, the vulnerability of forested ecosystems has been quantified by analysing how vegetation response, described, for example, with individual TRW time series or TRW chronologies, changes with environmental conditions, such as temperature and soil water availability (Lloret et al , Lévesque et al , Fang and Zhang , Serra‐Maluquer et al ). Recently, temporal dynamics of tree‐ and landscape‐level ecophysiological variables describing vegetation growth have been found to provide new insights into drought‐induced tree mortality and were used to reveal early‐warning signals of such type of disturbances (Camarero et al , Cailleret et al , , Rogers et al ).…”
Section: Discussionmentioning
confidence: 99%